(untitled) (RIAF. International Journal of Physical Activity, 2024)
Spinocerebellar Ataxia Type 2 (SCA2) is a genetic disorder with an autosomal dominant inheritance pattern, characterized by cerebellar atrophy associated with early hyporeflexia, slow saccadic movements, severe postural tremor, peripheral neuropathy, and other multisystemic features. This research reveals the role of Cuban healthcare professionals in adhering to the principles of medical ethics in their daily practice within the rehabilitation specialty for patients with Spinocerebellar Ataxia Type 2.